Cross Country Skiing: A sport for life. Long-Term Athlete Development Guide (Cross Country Canada, 2007)
Cross Country Canada is pleased to present its Long-Term Athlete Development (LTAD) Guide, "Cross-Country Skiing - A Sport for Life". This document introduces and explains the conceptual framework for athlete development that will provide essential guidance for Cross Country Canada, its divisions, clubs and individual members as we pursue the shared vision of establishing a sport system that is in the forefront of theory and practice. Cross Country Canada`s LTAD Guide, which is consistent with Sport Canada`s Long-Term Athlete Development Resource Paper but customized to cross-country skiing, is a catalyst for change and improvement that can help our sport achieve its goals of fostering both life-long participation and international excellence. To reach these goals will require: • A cooperative partnership between Cross Country Canada, its member divisions and clubs, within a sport system that recognizes and facilitates the roles of all players, including both those that are integral to CCC and those that are external to the organization (e.g. multi-sport organizations, community recreational organizations, schools, universities, etc.). • Systematic coaching development at all levels. • An effective athlete development framework from grassroots to elite levels. • Programs tailored specifically to an athlete`s development stage. • Long term strategies rather than a short term focus. In essence, Cross Country Canada`s LTAD concept will become the touchstone against which the relevance and effectiveness of all operations, functions and supporting systems within our sport will be measured. The concept clearly delineates "what needs to be done" and "why", if our sport is to flourish. Decisions and actions that determine "how it will be done" and "by whom" will create a comprehensive roadmap to success. Ultimately, by understanding and adhering to LTAD principles and practices, an optimal developmental environment for current and future cross-country skiers will be established.